Effects of Variety, Spacing and Nitrogen Application on Chickpea (Cicer arietinum) Growth and Yield in Embu County, Kenya - Wafula, Judith N.; Mugendi, Fredrick N.; Nthakanio, Paul N.; Mosioma, Jeremiah O.; Onyari, Charles N. (My University, 2022)
Chickpea is a pulse crop that is rich in proteins and helps in fulfilling the requirement of protein for vegetarian people thus yield maximization needed. This study aimed to determine the effects of spacing, nitrogen rates, and their interactive effects on the growth and productivity of the selected chickpea varieties. Field experiments were conducted at Mwea, Kenya between 2017 and 2018 involving four varieties (Saina K, Mwanza 2, Chaina I and Chaina III) at a spacing of 50x10cm, 50x20cm, and 50x30cm, and starter nitrogen-fertilizer application rates 0kg, 30kg, 60kg, and 90kg ha -1 Starter nitrogen fertilizer . A split-split plot design arranged in a 4x3x4 layout was used in the current study. Data related to plant height, biomass, grain yield, and harvest index were collected and subjected to statistical analysis by GLM in SAS 9.4 computer software. Variations occurred in measured traits like the height of crops (34.8138.00cm), biomass yield (3.31 - 8.08t ha Interactions Yield -1 ), seed yield (0.14 to 1.9t ha -1 ), and percent harvest index (5 - 45%) was reported. Mwanza 2 expressed the highest plant height, biomass, and grain yield. The highest plant biomass was obtained under 50x10cm spacing, while the highest grain yield weight was reported under 50x30cm spacing x 60kg N ha -1 . From the results of the study, it can be concluded that the highest enhanced growth and productivity of chickpea were realized at interactions of Mwanza 2x50x10cmx90kg ha -1 nitrogen rate in the study area.
Keywords: Chickpea; Growth; Spacing; Starter nitrogen fertilizer; Interactions; Yield